Conjugate mixed convection of a micropolar fluid over a vertical hollow circular cylinder - Ahmed, Alliche Sid; Ayoub, Bennia; Manal, Bouaziz Amina; Najib, Bouaziz Mohamed (Zielona Góra: Uniwersytet Zielonogórski)
This work conducts a numerical examination into the influence of a magnetic field and viscosity dissipation on the movement of a micropolar fluid over the surface of a vertical, hollow circular cylinder via conjugate mixed convection. In this investigation, we obtained a numerical solution for a non-linear differential equations-based modeling system by employing MATLAB and the bvp4c solver, which operates on a two-equation model.
Keywords: micropolar fluid; conjugate heat transfer parameter; viscous dissipation; magnetic field; buoyancy effect; vertical hollow circular cylinder